The difference of student’s activities and learning outcome with problem based learning using macromedia flash and handout - Desi Natalia Purba; Marini Damanik; Saronom Silaban; Lisnawaty Simatupang (Jurnal Pendidikan Kimia (JPKim), 2018)
This study aimed to determine the difference of student’s activities and learning outcome with PBL using macromedia flash and handout. The sample were selected using purposive sampling into experimental group I and experimental group II with 60 students. The experimental group I used the PBL using macromedia flash, while the experimental group II used the PBL using handout. The results indicated that the mean scores of student’s activities and learning outcome in the experimental group II were significantly higher than those in the experimental group I. Thus, there was a difference in student’s activities and learning outcome.  The correlation test between student’s activities and learning outcome presented that the experimental group I rcount>rtable (0.625>0.361) and the experimental group II rcount>rtable (0.683>0.361), it concluded that there was a positive correlation between student’s activities and learning outcome with PBL using macromedia flash and handout.Keywords:activities; difference; handout; macromedia flash; learning outcome; PBL